2016
DOI: 10.1007/s00464-016-4790-4
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia after single-incision laparoscopic cholecystectomy: incidence and predictive factors

Abstract: After SILC, we noted an incisional hernia rate of 8 %. To decrease the risk of developing that specific complication, SILC should only be proposed to young and non-obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…It has been argued against single port laparoscopy that there could be a higher rate of incisional hernia. [26][27][28][29][30][31] We did not find any such difference, and we actually believe that it is easier to close the fascial wound after single port laparoscopy because the larger skin incision facilitates the closing. Longer follow-up time should in any case be employed to re-evaluate whether incisional hernia rates continue to be equal in both groups.…”
Section: Discussionmentioning
confidence: 66%
“…It has been argued against single port laparoscopy that there could be a higher rate of incisional hernia. [26][27][28][29][30][31] We did not find any such difference, and we actually believe that it is easier to close the fascial wound after single port laparoscopy because the larger skin incision facilitates the closing. Longer follow-up time should in any case be employed to re-evaluate whether incisional hernia rates continue to be equal in both groups.…”
Section: Discussionmentioning
confidence: 66%
“…Christoffersen et al demonstrated similar hernia rates of 4% in the SLC group and 6% in the MLC group [14]. Julliard et al analysed the occurrence and risk factors for incisional hernias and showed a hernia rate of 7.9% after a mean follow-up of 41 months [52]. Bury et al examined the contradiction in occurrence of incisional hernia and compared the works of Antoniou et al and Christoffersen et al He recognized both studies as equivalent in their level of evidence and stated the need for long-term investigations of this topic [13].…”
Section: Discussionmentioning
confidence: 93%
“…We were unable to evaluate this variable among the selected studies since this information was not reported. On this issue, the literature shows conflicting data and several papers reported a higher number of wound complications, including a significant risk of developing port site hernias [26, 27]. The introduction of microlaparoscopic instruments that require trocars with a small diameter may enhance the cosmetic outcomes of conventional laparoscopy.…”
Section: Discussionmentioning
confidence: 99%